新移民教育課程政策的侷限與突破 Limits and Breakthrough of Curriculum Policy Surrounding Education for New Immigrants in Taiwan - 黃政傑 Jenq-Jye Hwang (Journal of Curriculum Studies, 2015)
自1999年以來，國內陸續推動三項重要的新移民教育政策，以因應不斷增加的新移民人口，協助其語言、文化學習及生活適應，並開展多元文化社會。其後教育部補助大學推動新移民之原生社會文化、公民與人權及健康醫療教學發展計畫，推動新住民語文樂學活動實施計畫，均與新移民教育的發展息息相關。本研究分析這些計畫內容，討論及反省其中課程政策的侷限所在，提出強化整合力、課程規劃系統化、東南亞社會文化融入正式課程、多語環境的整合經營、遠距教學模式的採用、課程教學資源建置管理、多元文化的師資培育及專業人才培育、課程政策的研究和評鑑、經費績效和行政負荷的因應等新移民教育課程改革方向。 This article aims to achieve three things. First, it attempts to analyze the content of important plans for the education of new immigrants (ENI) carried out by Ministry of Internal Affairs and Ministry of Education in Taiwan, along with local governments, schools, universities, NGOs and other educational institutes for new immigrants education. Second, it analyzes the curriculum policies surrounding these plans for new immigrants, and reflects on their features and limits. It is concluded that the improvement of curriculum policies and related measures for ENI is necessary. Finally, this article proposed several suggestions for curriculum innovations in the near future.